Pengaruh Kompetensi Pedagogik Tutor Terhadap Perkembangan Kognitif Peserta Didik Program Kesetaraan Paket C di UPT SKB Kabupaten Gresik - Herdiyanti, Farah Ayu; Susilo, Heryanto (J+PLUS UNESA, 2024)
The tutor's pedagogical competence has a very important role in the cognitive development of students. The aim of this research is to examine the influence of tutors' pedagogical competence on the cognitive development of package C equivalency program students at the Gresik Regency Learning Activity Studio Technical Implementation Unit. This research uses a quantitative method of the causal comparative type, with a Product Moment Correlation analysis technique with sampling using the Slovin formula, namely there are 22 tutors and 48 package C students. The research location is in the Technical Implementation Unit of the Gresik Regency Learning Activities Studio with data collection techniques in the form of questionnaires, observation and documentation. The correlation test carried out produced a correlation coefficient value of 0.429, meaning that the correlation coefficient value of the tutor's pedagogical competence had a positive and moderate influence on the cognitive development of package C equivalency program students at the Gresik Regency Learning Activity Studio Technical Implementation Unit. Therefore, if the tutor's pedagogical competence increases in learning, the students' cognitive development will be more focused.